2019
DOI: 10.1093/jxb/erz245
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone synthase is ubiquitinated and degraded via interactions with a RING-H2 protein in petals of Paeonia ‘He Xie’

Abstract: Flavonoids are secondary metabolites widely distributed among angiosperms, where they play diverse roles in plant growth, development, and evolution. The regulation of flavonoid biosynthesis in plants has been extensively studied at the transcriptional level, but post-transcriptional, translational, and post-translational control of flavonoid biosynthesis remain poorly understood. In this study, we analysed post-translational regulation of flavonoid biosynthesis in the ornamental plant Paeonia, using proteome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 86 publications
(110 reference statements)
2
28
0
Order By: Relevance
“…At present, more and more genes related to flavonoid biosynthesis pathway have been identified in some plant species: PsDFR , PsANS and PhCHS in peony [ 15 , 56 ]; CitCHS in citrus [ 47 , 57 ]; MiCHS , MiCHI and MiF3H in mango [ 58 ]; SbCHS , SbCHI and SbF3H in Selaginella officinalis [ 59 ]; CHS-A , CHS-B and AcFLSs in onion [ 60 ]; AgMYB1 in celery [ 61 ]; GbFLS in ginkgo biloba [ 62 , 63 ]; SmCHS , SmCHI and SmFNS in Salvia miltiorrhiza [ 50 ]; MaCHS in mulberry [ 64 ]; CtC4H2 , CtCHS3 , CtCHI3 , CtF3H3 and CtF3H1 in safflower [ 65 ]; CsMYB6A and CsUGT72AM1 in purple leaf tea [ 66 ]; AaFLS1 in Artemisia annua [ 67 ]. In order to explore the candidate genes that affecting cucumber peel yellowing, we further analyzed six DEGs involved in phenylpropionic acid, flavonoid, isoflavonoid, flavone and flavonol biosynthesis according to the relevant network map ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, more and more genes related to flavonoid biosynthesis pathway have been identified in some plant species: PsDFR , PsANS and PhCHS in peony [ 15 , 56 ]; CitCHS in citrus [ 47 , 57 ]; MiCHS , MiCHI and MiF3H in mango [ 58 ]; SbCHS , SbCHI and SbF3H in Selaginella officinalis [ 59 ]; CHS-A , CHS-B and AcFLSs in onion [ 60 ]; AgMYB1 in celery [ 61 ]; GbFLS in ginkgo biloba [ 62 , 63 ]; SmCHS , SmCHI and SmFNS in Salvia miltiorrhiza [ 50 ]; MaCHS in mulberry [ 64 ]; CtC4H2 , CtCHS3 , CtCHI3 , CtF3H3 and CtF3H1 in safflower [ 65 ]; CsMYB6A and CsUGT72AM1 in purple leaf tea [ 66 ]; AaFLS1 in Artemisia annua [ 67 ]. In order to explore the candidate genes that affecting cucumber peel yellowing, we further analyzed six DEGs involved in phenylpropionic acid, flavonoid, isoflavonoid, flavone and flavonol biosynthesis according to the relevant network map ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, joint analysis based on multifunctional “omics” data has been demonstrated to be a powerful tool to clarify different aspects of plant developmental biology as well as environmental responses [ 14 , 15 , 16 ], such as drought stress response [ 4 ], effects of grafting different rootstocks on fruit flavor [ 1 ] and astringency-related gene mining in cucumber [ 17 ]. Furthermore, transcriptome and metabolome analysis have been widely used to identify signal pathway and mechanisms controlling pigment accumulation in plant pulp or peel.…”
Section: Introductionmentioning
confidence: 99%
“…So, too, must there be information at the level of the individual protein components, including reorganization of intracellular interaction networks and localization. Even the role of post-translational modifications, as in the case of the phenylpropanoid and flavonoid pathways, is just beginning to be uncovered 39,40,54,69 . Technologies to address these questions in a comprehensive manner are increasingly within reach and will help write a new understanding of the processes by which cells execute re-equilibration of their metabolic status, both as part of immediate responses and to achieve new long-term steady states.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest post-translational regulation as a possible mechanism for flavonoid accumulation because (i) a quantitative increase was detected simultaneously in a broad range of flavonoids, including colorless flavonoids by metabolic analysis in AD, implying the up-regulation of early biosynthetic gene(s) and (ii) the enrichment of genes encoding proteins involved in post-translational regulation (notably F-box proteins) among down-regulated DEGs, without the clear transcriptional up-regulation of flavonoid biosynthetic genes, was observed by transcriptome analysis. Increasing evidence for the involvement of the post-translational regulation of flavonoid biosynthetic genes, especially early flavonoid biosynthetic genes, in the determination of flavonoid content, has been reported for many crops [13][14][15]53,54]. Gu et al [54] reported that CHS, which catalyzes an early step in the flavonoid biosynthetic pathway, contained the largest number of ubiquitination sites among genes in the same pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence for the involvement of the post-translational regulation of flavonoid biosynthetic genes, especially early flavonoid biosynthetic genes, in the determination of flavonoid content, has been reported for many crops [13][14][15]53,54]. Gu et al [54] reported that CHS, which catalyzes an early step in the flavonoid biosynthetic pathway, contained the largest number of ubiquitination sites among genes in the same pathway. In addition, Zhang et al [14,15] showed that PAL, the enzyme responsible for the first step of the phenylpropanoid pathway, is a common target of four F-box proteins, thus the knock-out mutation of genes encoding these proteins results in the accumulation of a broad range of flavonoids.…”
Section: Discussionmentioning
confidence: 99%